Clinical Evaluation of Intra-Articular Injection of Chondroitin Sulfate and Sodium Hyaluronate in the Management of Degenerative Osteoarthritis of Temporomandibular Joint - Elsayed, Lubna K.; Elsharrawy, Eman; Elsholkamy, Mohammed; Tawfik, Mona K. (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: This study aims to evaluate the effectiveness of intra-articular injection of chondroitin sulfate and sodium hyaluronate in cases of temporomandibular joint (TMJ) degenerative osteoarthritis. MATERIAL AND METHODS: Thirty patients ASA I of both sexes, who were selected from outpatient clinic of Oral Surgery Department, Faculty of Dentistry – Suez Canal University, complaining of painful TMJ, presence of unilateral or bilateral TMJ pain, impairment of jaw movements, and joint sounds. Clinical examination was performed to all patients and pre-operative measurements of visual analog scale (VAS) for morning pain, pain with movement and spontaneous pain, maximum mouth opening, and presence or absence of clicking. Patients were randomly divided into two groups; (a) Study group consisted of 15 patients, they had intra-articular injection of chondroitin sulfate and sodium hyaluronate once weekly for 3 weeks and (b) control group consisted of 15 patients, they had intra-articular injection of sodium hyaluronate once weekly for 3 weeks. Post-operative measurements of VAS for previous pain types, maximum mouth opening, and clicking were obtained at 1 month, 3 months, and 6 months post-injection. RESULTS: There was a statistically significant reduction of all types of pain in the study group compared to the control group at all time intervals (p ≤ 0.05), for maximum mouth opening, there was a significant improvement in mouth opening in the study group for all time intervals (p ≤ 0.05), but for the clicking, there was not statistically significant difference between the study and control groups after 1 month, 3 months, and 6 months. The difference between groups was barely statistically significant (p = 0.05). CONCLUSION: Intra-articular injection of a combination of chondroitin sulfate and sodium hyaluronate is an effective tool in reducing pain, clicking, limited mouth opening, and other symptoms associated with degenerative TMJ diseases.